2021
DOI: 10.52673/18570461.21.1-60.06
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Waste Processing Procedure of the Beer Industry and Obtaining Lipid Preparation From Yeast Biomass

Abstract: Currently, special attention is paid to the use of industrial by-products, in particular those obtained in huge quantities in the brewing and wine making process, as a source for the production of natural preparations with high biological value. In this study are presented results related to the recovery of beer yeast biomass from the sediments of the beer industry, by obtaining lipid extracts with valuable biochemical composition. Thus, applying the optimized autolysis method, with the use of sodium phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was found that the yeast contained significant amounts of proteins, including essential and immunoactives amino acids, carbohydrates, especially proteomannans and β-glucans, lipids, phospholipids, sterols, waxes, various trace elements, and had a high antioxidant activity. The results demonstrated that the yeast was an excellent source of biologically active substances and could be used for obtaining biologically active preparations (Beșliu et al, 2020;Chiseliţa et al, 2020;Tofan et al, 2021). Thus, the purpose of this research was to evaluate the biochemical composition and antioxidant activity of the different preparations, obtained from the yeast biomass of the beer industry waste.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the yeast contained significant amounts of proteins, including essential and immunoactives amino acids, carbohydrates, especially proteomannans and β-glucans, lipids, phospholipids, sterols, waxes, various trace elements, and had a high antioxidant activity. The results demonstrated that the yeast was an excellent source of biologically active substances and could be used for obtaining biologically active preparations (Beșliu et al, 2020;Chiseliţa et al, 2020;Tofan et al, 2021). Thus, the purpose of this research was to evaluate the biochemical composition and antioxidant activity of the different preparations, obtained from the yeast biomass of the beer industry waste.…”
Section: Introductionmentioning
confidence: 98%